Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1095-8649.2008.02016.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the pelagic shark‐fin trade in north‐central Chile by genetic identification and trader surveys

Abstract: Shark fins have become a highly valued commodity with the major Asian fin-trade centres supplied from global sources, including Chile. With growing concerns about the resilience of shark populations to heavy fishing pressure, there is a need for better information on shark landings to aid management efforts. In the widespread absence of shark landing records especially by species, monitoring the fin trade has been proposed as a way to assess species exploitation levels. Here, the first species assessment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 10 publications
1
17
0
4
Order By: Relevance
“…Besides, I. paucus and I. oxyrinchus exhibit significant overlap in their distribution range, sharing similar ecological niches, fishing threats, and external morphological characteristics (Compagno 2001, Compagno et al 2005. Sebastian et al (2008) reported I. paucus by molecular DNA analysis of fins obtained from fin-storage warehouses in Chile that suggest unreported captures of this species. This background information suggests an extension of the known species range to more temperate waters, which until now was thought to be limited to tropical areas.…”
Section: Ebert 2001) the Number Of The Corresponding Figure Ofmentioning
confidence: 99%
“…Besides, I. paucus and I. oxyrinchus exhibit significant overlap in their distribution range, sharing similar ecological niches, fishing threats, and external morphological characteristics (Compagno 2001, Compagno et al 2005. Sebastian et al (2008) reported I. paucus by molecular DNA analysis of fins obtained from fin-storage warehouses in Chile that suggest unreported captures of this species. This background information suggests an extension of the known species range to more temperate waters, which until now was thought to be limited to tropical areas.…”
Section: Ebert 2001) the Number Of The Corresponding Figure Ofmentioning
confidence: 99%
“…En este sentido, Hernández et al (2009) han sido una excepción, puesto que estos autores emplearon la aleta caudal (considerando además otros elementos) enfocados en la determinación de la aleta caudal de algunas especies involucradas en el comercio de aletas, restringiéndose así a unas pocas especies de interés comercial como son: Prionace glauca, Isurus oxyrhinchus y Lamna nasus. Así mismo, Sebastian et al (2008) y Hernández et al (2010, obtuvieron la caracterización de algunas especies pelágicas, en las costas de Chile mediante la determinación genética de las aletas de tiburones, incluyendo la caudal.…”
Section: Discussionunclassified
“…Sin embargo, tanto para C. obscurus como para C. falciformis, mediante nuevos antecedentes bibliográficos, se puede confirmar su presencia en el centro norte de Chile, aumentando las especies chilenas de 56 (Sáez et al 2010) a 58 especies (Sebastian et al 2008, FISHWISE 2011 2 ).…”
Section: Discussionunclassified
“…Al respecto, cabe señalar la confirmación de la presencia de Isurus paucus en la zona centro de Chile, captura efectuada el 2004 en Caldera y Paico, y cuya presencia fue también registrada en marzo del año 2007 en el Pacífico suroeste (32º30'S, 74º30'W) en Caleta Portales, Valparaíso (Bustamante et al 2009), que junto con Sphyrna lewini (conocida en el Perú) no han sido confirmados en los registros de pesquerías artesanales e industrial, aumentando el rango de distribución de ambas especies (Sebastian et al 2008).…”
Section: Discussionunclassified